So vast, so beautiful a land; Louisiana and the Purchase. - Sprague, Marshall (Boston, Little, Brown, 1974)
Recounts how explorers discovered the Mississippi region and discusses the political, economic, and social factors that led to the Louisiana Purchase.
Bibliography: p. 370-381.
Keywords: Louisiana Purchase; Mississippi River Valley -- History -- To 1803.